Comparison of Functional Outcome of Locking Plate versus External Fixation in Management of Comminuted Intra Articular Fracture of Proximal Tibia: Locking Plate versus External Fixator - Shah, Syed Usman; Saud, Abdul Munaf; Rashid, Muhammad; Napar, Abdul Rasheed; Zia, Osama Bin; Abidi, Syed Abdur Rub (Pakistan Journal of Health Sciences, 2025)
The surgical management of Schatzker type V or VI tibial plateau fractures can be challenging, and complications may include compartment syndrome, soft-tissue and ligament damage, and neurovascular injury. A successful course of treatment necessitates articular cartilage regeneration, biological integrity preservation, mechanical axis realignment, joint stabilization, and mobility preservation. Objective: To compare the outcomes of locking plate vs. external fixation in management of comminuted intra articular fracture of proximal tibia. Methods: In this quasi experimental study 82 patients of proximal tibia fracture were presented. Patients were admitted to orthopedic department and were included after getting informed written consent. Two groups were created, in group I 41 patients received locking plate and 41 patients of group II received external fixation. Outcomes among both groups were compared after treatment. SPSS version 23.0 was used to analyze all data. Results: There were majority males in both groups. Patients of group I had mean age of 36.13 ± 10.63 years and in group II mean age was 34.8 ± 7.49 years. Postoperative functional outcome was significantly better in group I as compared to group II with p value <0.05. As per Rasmussen’s clinical functional knee score, group I had higher score 23.61 ± 6.154 as compared to group II 21.45 ± 6.187 with p value <0.03. Post-operative frequency of infection was lower in group I as compared to group II with p value <0.02. Conclusion: It was concluded that in this study that internal locking plate showed better outcomes in terms of functional results while had higher blood loss and longer operative time as compared to external fixation.